FORMATION OF MENTAL POTENTIAL PROCESSES OF CHILDREN IN PRESCHOOL AGE - Nurullayeva Nodira Nomonjonovna (Journal of new century innovations, 2023)
Annotation: This article describes about the formation of mental potential processes of children at the age of preschool education, games for the growth of memory, various activities, problems of inclusive education in preschool education and measures taken by the state to eliminate them.